PEMANFAATAN PLANKTON DAN PERIPHYTON SEBAGAI BIOINDIKATOR LIMBAH ORGANIK RUMAH TANGGA DI MUARA SUNGAI KAKAP KABUPATEN KUBU RAYA KALIMANTAN BARAT - Patrisia Marniati; Mardan Adijaya; Widadi Padmarsari (Fakultas Pertanian Universitas Tanjungpura, 2020)
The Kakap River estuary is a densely populated estuary with various kinds of community activities, which have the impact of reducing water quality and causes pollution. To see the level of pollution in these waters, one of the methods used is using plankton and periphyton as bioindicators. The purpose of this study was to determine the class composition, and saprobic coefficient for plankton and periphyton in the Kakap River Estuary, Kubu Raya Regency, West Kalimantan. The method used was purposive random sampling. The research location is divided into 4 stations based on the estimated opportunity opportunities information. The research was conducted in March, April and June 2020 at the Kakap River Estuary, Kubu Raya Regency, West Kalimantan. Based on the research, the plankton composition found consisted of 10 phytoplankton classes and 8 classes including zooplankton. The periphyton composition found consisted of 8 classes. The saprobic coefficient of plankton is in the α / β-mesosaprobic phase with moderate pollution levels of organic and inorganic materials. The saprobic coefficients of the periphyton phase are in the α – mesosaprobic phase and the poly- microbic phase with the pollution level of heavy enough to very heavy organic matter. Key words: Plankton, Periphyton, Bioindicators, Organic Waste.